2014
DOI: 10.1073/pnas.1409836111
|View full text |Cite
|
Sign up to set email alerts
|

Bloom of resident antibiotic-resistant bacteria in soil following manure fertilization

Abstract: The increasing prevalence of antibiotic-resistant bacteria is a global threat to public health. Agricultural use of antibiotics is believed to contribute to the spread of antibiotic resistance, but the mechanisms by which many agricultural practices influence resistance remain obscure. Although manure from dairy farms is a common soil amendment in crop production, its impact on the soil microbiome and resistome is not known. To gain insight into this impact, we cultured bacteria from soil before and at 10 time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
268
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 503 publications
(298 citation statements)
references
References 55 publications
25
268
3
2
Order By: Relevance
“…The relationships between the quality parameters determined here in all the amendments were studied by means of a principal component analysis (PCA), using Canoco 5 (Ter Braak and Smilauer, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationships between the quality parameters determined here in all the amendments were studied by means of a principal component analysis (PCA), using Canoco 5 (Ter Braak and Smilauer, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, emerging contaminants (e.g., pesticides and their metabolites, pharmaceuticals, personal and house care products, food additives, industrial products and wastes, nanomaterials) have become a matter of much concern (Gomes et al, 2017). For example, the dissemination of antibiotic resistance genes, which can occur via the application of manure-and sewage sludge-derived amendments to agricultural soil (Martínez-Carballo et al, 2007;Udikovic-Kolic et al, 2014), is currently a matter of much concern due to the risk of transfer of antibiotic resistance genes to human pathogens (Marshall and Levy, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Amendment of soils with manure from antibiotic-treated animals has been frequently reported as an important route by which ARGs enter the environment and food system (Ghosh and LaPara 2007;Heuer et al 2008). However, recent studies suggested that high frequencies of ARGs (such as β-lactamases and tetracycline-resistance genes) are encountered in manure from dairy cows receiving no administration of veterinary antibiotics (Kyselkova et al 2013;Udikovic-Kolic et al 2014). Similarly, the cattle manure samples used in this study, which have not been treated with antibiotics, were also found to be a major source of diverse and abundant ARGs.…”
Section: Diversity and Abundance Of Args In Soil And Manure Samplesmentioning
confidence: 99%
“…Therefore, the selective pressure of residual antibiotics will rapidly vanish over time, and other mechanisms might exist to influence the soil resistance patterns in the absence of antibiotic selection pressure. In fact, previous studies have suggested that manure amendment of soil adds a considerable amount of manure-derived ARGs on transferable plasmids (Heuer, Schmitt and Smalla 2011a), even if the producing animals have never been treated with antibiotics (D'Costa et al 2011;Udikovic-Kolic et al 2014). Resident soil antibiotic-resistant bacteria were also found to significantly increase following application of manure from cows without antibiotic treatment history .…”
Section: Introductionmentioning
confidence: 96%
“…Multiple studies have shown that animal manure fertilization increases the abundance of drugresistant bacteria and the frequency of antibiotic resistance genes in soils (Udikovic-Kolic, 2014;Marti, 2013;Gao, 2015;Garder, 2014). Underlying mechanisms are obviously more complex than just the simple addition of antibiotic resistant bacteria to farmland and depend on factors like bacterial fitness and transferability of genetic elements.…”
Section: Farm Animal Disease Treatmentmentioning
confidence: 99%